Molecular mechanisms underlying the role of hypoxia-inducible factor-1 α in metabolic reprogramming in renal fibrosis - Wei, Xuejiao; Hou, Yue; Long, Mengtuan; Jiang, Lili; Du, Yujun (Frontiers in Endocrinology, 2022)
Renal fibrosis is the result of renal tissue damage and repair response disorders. If fibrosis is not effectively blocked, it causes loss of renal function, leading to chronic renal failure. Metabolic reprogramming, which promotes cell proliferation by regulating cellular energy metabolism, is considered a unique tumor cell marker. The transition from oxidative phosphorylation to aerobic glycolysis is a major feature of renal fibrosis. Hypoxia-inducible factor-1 α (HIF-1α), a vital transcription factor, senses oxygen status, induces adaptive changes in cell metabolism, and plays an important role in renal fibrosis and glucose metabolism. This review focuses on the regulation of proteins related to aerobic glycolysis by HIF-1α and attempts to elucidate the possible regulatory mechanism underlying the effects of HIF-1α on glucose metabolism during renal fibrosis, aiming to provide new ideas for targeted metabolic pathway intervention in renal fibrosis.